İdari davalarda taraf ehliyeti subjektif ehliyet - Gümüş, Ferhan (My University, 2003)
Hukuk Devletini gerçekleştirmenin en etkili yöntemlerinden biri idarenin hukuka uygun davranmasını sağlamaktır. Bu da idarenin yargısal denetimiyle mümkündür. Yargısal denetim idari davalarla gerçekleştirilmektedir. Ancak dava açabilmek için de çeşitli şartların gerçekleşmesi gerekir. Bunların başında dava açacak kişinin bu davayı açmaya ehil olması gelmektedir. Ehliyet çeşitli şekillerde ortaya çıkabilmektedir. Medeni hukuk alanındaki ehliyet “objektif ehliyet”, idari yargı hukuku alanındaki ehliyet “subjektif ehliyet” olarak adlandırılmaktadır. İdari yargıda dava açabilmek için her iki ehliyete de sahip olmak gerekir. Yargı yerlerinin ehliyet kavramını dar veya geniş bir şekilde yorumlamaları idari davaların açılabileceği alanı daraltacak veya genişletecektir. Bu çalışmada kimlerin hangi koşullarla idari davalarda taraf olabileceği yargı kararlarından yararlanılarak ortaya konulmaya çalışılmıştır. One of the most effective ways of realizing the State of Law is to ensure that the administration acts in accordance with Law. This is possible with the legal inspection of administration. Legal inspection is realized by the administrative cases. However, certain conditions should be realized to be able to open a case. On top of these, the person who will open the case should be qualified to open this case. The license may arise in different circumstances. The license under the Civil Law is named as “objective license”, the license under the administrative court law is named as “subjective license”. To be able to open a case in administrative jurisdiction, it is necessary to have both licenses. The jurisdiction seats’ interpreting the concept of license in a narrow or wide manner will narrow or widen the scope where administrative cases can be opened. In this study, it has been tried to exhibited who can be parties in an administrative case under which circumstances, by making use of judicial decisions.
Keywords: Anayasa ve idare hukuku; Hukuk; Kamu Hukuku